Chemical reactions that go in the electrolysis processes of aqueous solution and liquefaction, as well as their conditions of going - Ishmanova Zohida Ubaydullayevna; M.B.Ayupova; M.A.Aripdjanova; G.A.Usmanova. (Open Academia, 2024)
This article explores the chemical reactions occurring during the electrolysis of aqueous solutions and the liquefaction processes. It focuses on the mechanisms behind these reactions, the conditions under which they proceed, and their industrial applications. Through a detailed literature review, this work summarizes the theoretical principles, methodologies, and the outcomes of experimental studies, offering a basis for further development in electrochemical and liquefaction technologies. The paper concludes by providing suggestions for optimizing these processes for energy efficiency and environmental sustainability.
Keywords: Electrolysis; aqueous solution; liquefaction